EFFECT OF MOTIVATION, ORGANIZATIONAL COMMITMENT AND JOB SATISFACTION TOWARDS OCB - MARTIN STARRY SOEHARDI; Karel Tjahjadi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
Every organization is required to move forward, develop and also survive in every condition to achieve the organization goals. Manpower is a human resource, which is an important factor in carrying out company’s vision, mission and also achieving organization goals that cannot be separated from an organization, both institutions and companies. Based on meeting with the owner of PT. X, performance appraisal of PT. X in 2019-2021 decreased and there is a research gap that examines motivation, organizational commitment and job satisfaction towards OCB. This research aims to examine and analyze the effect of motivation, organizational commitment and job satisfaction towards OCB. The samples used in this research are 81 respondents of PT. X. Sampling method used in this study is saturated sample and the method for data analysis ini this study used multiple linear regression analysis. Research data is primary data collected by distributing questionnaires and using Likert scale. The results of this research showed job satisfaction has a positive effect on OCB.